The effect of solar radiation on spermatozoa abnormality and motility in bulls - Sahin, Onur (Korean Society Animal Science & Technology, 2026)
The aim of this study was to investigate the effects of solar radiation on spermatozoa motility and abnormalities. The material of the study consisted of 28 bulls of the Holstein Friesian, Brown Swiss and Simmental breeds reared in a private AI center for artificial insemination, as well as the data of 1,539 collected ejaculations of these bulls and the meteorological data of the research area. The SPPS 25.0 program was used for statistical analysis. The differences between the solar radiation intensity groups for the concentration and proportion of distal midpiece reflex (DMR) and coiled tail (CT) spermatozoa were highly statistically significant (p < 0.01) and the differences found for the concentration and proportion of proximal drop (PD) spermatozoa were statistically significant (p < 0.05). In contrast, the differences found between the groups for CT spermatozoa were statistically insignificant (p > 0.05). The difference between the groups of solar radiation for the ratio of solve spermatozoa (SL) to abnormal spermatozoa was statistically significant (p < 0.01), while the differences for Static spermatozoa (ST), Progressive spermatozoa (PR), and motile spermatozoa (MO) spermatozoa ratios were statistically insignificant (p > 0.05). The differences observed between the temperature-humidity index groups in all abnormal spermatozoa ratios were not statistically significant (p > 0.05). The intensity of solar radiation was positively and significantly (p < 0.05) associated with ST spermatozoa, while it was negatively and significantly (p < 0.01) associated with MO and SL spermatozoa. There was a positive and significant (p < 0.01) association between solar radiation intensity and abnormal spermatozoa bent tail (BT), DMR, distal drop (DD) and proximal drop (PD), while CT showed a negative and significant (p < 0.05) association with spermatozoa. There was a positive and significant relationship between temperature-humidity index (THI) and ST motility traits, a negative and significant relationship with MO spermatozoa and a negative and significant relationship with SL spermatozoa ratio. There was a positive and significant relationship between THI and BT, DMR, DD and PD abnormal spermatozoa, while a negative and significant relationship was found with CT.
Keywords: Abnormal Spermatozoa; Bull Fertility; Semen Motility; Semen Quality; Solar Radiation; Core Temperature